A Qualitative Perspective on Anti-Doping: Mixed Methods Research - Mine Ömercioğlu; Alparslan Erman (Pamukkale University, 2023)
National and international anti-doping programs are carried out to protect athletes' health, establish an equal and fair competition environment, and defend the basic principles of sports. This study aims to determine the situation regarding the prevention of doping in sports in Türkiye and the recommendations that can be presented to the national sports administration on anti-doping in line with the findings to be obtained. The study was designed with the explanatory sequential design participant selection sub-design, a mixed method research. Three hundred-two people, determined by the purposeful sampling technique, participated in the research. After evaluating the quantitative findings obtained using the questionnaire technique, in-depth interviews were conducted for the qualitative part of the research with 12 people who met the criteria determined among all the participants. Descriptive statistics were used to analyze quantitative data, and theme analysis, descriptive analysis, content analysis, analytical generalization, and discourse analysis were performed in qualitative data analysis. As a result of this research, it is understood that training activities prepared to increase the knowledge and awareness level of sports professionals are considered a more effective method for doping prevention than criminal sanctions. In line with the findings obtained, it is understood that there is a need to establish an independent, multi-faceted anti-doping organization in which all relevant stakeholders are involved and a national action plan in which more importance is attached to guidance and training activities.